Functional and molecular determination of carbonic anhydrase levels in bovine and cultured human chondrocytes. - Swietach, P; Browning, J; Wilkins, R (2002)
In this study, bovine articular and human chondrocytes from the C-20/A4 cell line were tested for the functional activity and molecular presence of the enzyme carbonic anhydrase. This enzyme is classically considered to be important in the maintenance of high cellular buffering capacity by catalysing the slow attainment of equilibrium between CO(2) and HCO(3)(-). The first functional assay measured the rate of pH equilibration after administration of a fixed dose of CO(2) solution to cell lysates. Compared to positive controls (human erythrocytes, murine M1 cells and purified carbonic anhydrase), chondrocyte lysates attained equilibrium at a significantly slower rate, similar to the rate obtained with a negative control (Xenopus oocytes). A second functional assay studied CO(2) hydration kinetics in intact C-20/A4 cells, using a pH-sensitive fluorescent dye, as the CO(2) content of the extracellular solution was changed. It was shown that C-20/A4 cells accelerate hydration only to a small degree. Hydration kinetics were reduced to the spontaneous rate in the presence of acetazolamide. Western immunoblotting with isoform-nonspecific antibodies to carbonic anhydrase demonstrated weak staining in both bovine and human chondrocytes.